Nonsuicidal Self-Injury and Perfectionism: A Systematic Review - Gyori, Dora; Balazs, Judit (Frontiers in Psychiatry, 2021)
Background: Nonsuicidal self-injury (NSSI) and perfectionism mean a huge concern related to mental health and psychopathology. Recently, there has been a growing interest in research on the exploration of the association of perfectionism and NSSI, but till today there is no systematic review has been prepared in this topic. Aims: Therefore, we performed a systematic literature review of published studies that investigated the association between NSSI and perfectionism. Methods: The systematic search was made on PubMed, OVID Medline, PsychInfo, Scopus, and Web of Science. The search terms were (“nonsuicidal self-injury” OR “non-suicidal self-injury” OR NSSI OR “self-injury” OR “self-injurious behaviour” OR SIB OR “self-harm” OR “deliberate self-harm” OR DSH) AND (perfectionism). The inclusion criteria were as follows: written in English; reported empirical data; used validated self-report measures; investigated the association of nonsuicidal self-injury and perfectionism. There were no restrictions on participants regarding age, gender, race or ethnicity. Exclusion criteria: not written in English; was a review/meta-analysis; measured suicide behaviour; measured self-injury irrespective of motivation or suicidal intent; was not about the association between nonsuicidal self-injury and perfectionism. Results: After the screening process, 15 studies were included in our systematic review. The majority of studies (12) were published in the last 10 years. Nine (60%) recruited participants from community samples, four (26.7%) from clinical populations, and two (13.3%) both from community and clinical participants. Fourteen (93.3%) of the studies were cross-sectional studies, and one study contained a longitudinal investigation. The majority of studies included only or mainly female participants (62.3%-87.2%) and two studies contained a balanced male-female ratio population. Fourteen (93.3%) studies from the 15 studies found a significant positive association between NSSI and perfectionism. Limitations: The heterogeneity of used instruments makes it difficult to compare the results of involved studies. Only two studies investigated populations with balanced gender ratios. Only two studies examined both clinical and community populations. Clinical investigations enrolled mainly eating-disordered (ED) patients. Conclusions: The results of the current systematic review highlight the role of perfectionism in NSSI engagement. This systematic review may help the development of effective prevention initiatives and treatment strategies.